Computational studies of correlated 1D and 3D systems : a density functional theory approach - Akande, Akinlolu (Trinity College (Dublin, Ireland). School of Physics, 2011)
This thesis describes a number of theoretical investigations into the electric and magnetic properties of one-dimensional and three-dimensional correlated systems. Our studies are based on suitable and efficient implementations of different approximations to the exchange-correlation (XC) energy functional of ground state density functional theory (DFT).
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin